Subnational sectarianisation: clientelism, religious authority, and intra-religious rivalry in Aceh. Issue 2 (15th March 2021) - Permana, Yogi Setya
ABSTRACT: This contribution investigates the link between clientelism and intra-religious rivalry in post-conflict Aceh, Indonesia, through a sectarianisation thesis lens. Instead of utilising a theological approach or a primordialist perspective, this contribution analyses how contextual political drivers such as clientelism can serve as an alternative approach to comprehending intra-religious rivalry. I examine how the practices associated with clientelism contribute to sectarian rivalry by focusing on religious authority contestation in Aceh. This contribution argues that in Aceh's sharia (Islamic law) ecosystem, dominance within the official council of ulama (Islamic religious leaders) conveys the status of religious authority that, critically, confers access to state resources in both the political and economic spheres. In this context, discriminatory fatwas (legal opinion) and intolerant actions by the traditionalists directed against minority religious groups such as the Salafi community serve as essential tools in maintaining the status of religious authority. These actions are intertwined with state-based clientelism, as is seen in the allocation of funds for traditionalist-based Islamic boarding schools ( dayah ). The traditionalist ulama therefore have a keen interest in defending their status as religious authorities, as it secures their privileged access to state patronage.